2014
DOI: 10.1186/1471-2458-14-159
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status among patients visiting a tertiary care center in Riyadh, Saudi Arabia: a retrospective review of 3475 cases

Abstract: BackgroundVitamin D deficiency has been implicated in several chronic, non-communicable diseases independent of its conventional role in bone and calcium homeostasis. In this retrospective study, we determined the prevalence of vitamin D deficiency and its association to several cardiometabolic indices among patients visiting King Abdulaziz Medical City (KAMC), a tertiary hospital in Riyadh, Saudi Arabia.MethodsA total of 3475 charts of out-patient subjects who visited KAMC from September 2009 until December 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 47 publications
8
30
0
Order By: Relevance
“…Similar lab data-based study was carried out in neighbouring countries like India, Pakistan and Saudi Arabia. [20][21][22][23] 20 Similar large study from Pakistan involving 60,937 specimens revealed prevalence of vitamin D deficiency, defined as serum 25(OH)D <20 ng/mL to be 66.1%. 21 Smaller study with identical design found the prevalence of vitamin D deficiency (<20 ng/mL) and insufficiency (20-29.9 ng/mL) to be 60% and 27.6%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Similar lab data-based study was carried out in neighbouring countries like India, Pakistan and Saudi Arabia. [20][21][22][23] 20 Similar large study from Pakistan involving 60,937 specimens revealed prevalence of vitamin D deficiency, defined as serum 25(OH)D <20 ng/mL to be 66.1%. 21 Smaller study with identical design found the prevalence of vitamin D deficiency (<20 ng/mL) and insufficiency (20-29.9 ng/mL) to be 60% and 27.6%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no previous studies among Saudi adults have been carried out that focused on the relationship between vitamin D status and the risk of CHD. In Saudi Arabia, vitamin D deficiency is highly prevalent, even though there is plentiful sunlight throughout the year [17,18,19,20,21,22,23]. Several studies have reported low levels of vitamin D ranging from 8.4 to 11.6 ng/mL and from 8 to 16.6 ng/mL in males and females, respectively [17,18,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the prevalence of vitamin D deficiency was associated with age, and obesity, and positively correlated with calcium, albumin, and phosphorus. It was negatively correlated with alkaline phosphatase and PTH levels (16). This present study showed a higher prevalence of vitamin D deficiency among the Saudi population in Al-Madinah Al-Munawarah (91%) than what was reported by Alfawaz et al (2014) in Riyadh (72.4.1% in males).…”
Section: Discussionmentioning
confidence: 99%
“…It was negatively correlated with alkaline phosphatase and PTH levels (16). This present study showed a higher prevalence of vitamin D deficiency among the Saudi population in Al-Madinah Al-Munawarah (91%) than what was reported by Alfawaz et al (2014) in Riyadh (72.4.1% in males). Furthermore, this present study has not only detected the prevalence of vitamin D deficiency among the Saudi population, but also compared the high prevalence with those of the non-Saudi population living in the same environment via a prospective study design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation